Investigating the Influence of a Product-Harm Crisis on Consumer Buying Behaviour: A Focus on the Listeriosis Crisis - Mgoduka, Siyasanga; Heeralal, Shalen (International Review of Management and Marketing, 2023)
Product-harm crises often lead to negative publicity which substantially affects the consumers intention to make a purchase. This study attempts to investigate the influence of a product-harm crisis on consumer purchasing behaviour. Consumers are the most essential stakeholders for any organization, their core behavior is very vital for financial affluence and successful marketing. This study aims to investigate the influence of a product-harm crisis on consumer purchasing behaviour, with reference to the Listeriosis crisis. Data was collected from 384 randomly selected food retail store shoppers at empangeni and Richards Bay, using a quantitative research approach. Data was collected through the use of questionnaires. The findings from this study revealed that there was a positive significant correlation between the level of education and post-purchase behaviour. These findings suggest that consumers that are more educated tend to be more critical in analyzing a crisis. This study contributes to the existing body of knowledge on brand management by examining the influence of a product-harm crisis on consumer purchasing behaviour. The research concludes that brands should always have a positive relationship with consumers. Mainly because this current study has revealed that consumers response to a brand crisis is determined by the relationship they share with the brand along with the prior expectations they had about the brand.